A dialogue in support of social justice - Daniel John Anderson; Susan T. Gardner (Praxis & Saber)
There are kinds of dialogue that support social justice and others that do the reverse. The kinds of dialogue that support social justice require that anger be bracketed and that hiding in safe spaces be eschewed. All illegitimate ad hominem/ad feminem attacks are ruled out from the get-go. No dialogical contribution can be down-graded on account of the communicator’s gender, race, or religion. As well, this communicative approach unapologetically privileges reason in full view of theories and strategies that might seek to undermine reasoning as just another illegitimate form of power. On the more positive side, it is argued in this paper that social justice dialogue will be enhanced by a kind of “communicative upgrading,” which amplifies “person perception,” foregrounds the impersonal forces within our common social spaces rather than the “baddies” within, and orients the dialogical trajectory toward the future rather than the past. Finally, it is argued in this paper that educators have a pressing responsibility to guide their students through social justice dialogue so that their speech contributes to the amelioration of injustice, rather than rendering the terrain more treacherous.